Profit-sharing and innovation - Kris Aerts; Kornelius Kraft; Julia Lang (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We investigate the effect of profit-sharing on product and process innovation. Profit-sharing is a credible commitment of the companies to let the employees participate in any efficiency gain. Resistance against technical progress becomes less plausible. Moreover, employees are stimulated to share their specific information advantage on possibilities to optimize the production process and products with the management. We take account of possible selectivity effects and using survey data on German companies with and without profitsharing in a conditional difference-in-differences framework, we test our hypothesis by comparing measures of innovativeness. Based on matching (selectivity on observable covariates) in a static comparison firms with a share system show both more product and process innovations. In a dynamic setting, we find that the introduction of profit-sharing only spurs product innovation.
urn:nbn:de:bsz:180-madoc-353686
Keywords: L23; L25; O31; O32; 330; Profit Sharing; Innovation; Matching; Difference-in-Differences